The Utilization of Canva Application in Innovative Learning For Elementary School Teachers - Putri Riyanto, Miranda Ade Tias; Selsha Juliana Dwi Putri (Yayasan Insan Mulia Bima, 2024)
The use of information and communication technology is very important in the digital era. This research explores the use of Canva in innovative learning for prospective elementary school teachers. This research investigates the impact of Canva on teacher creativity, student motivation and digital skills development. A qualitative approach through literature analysis was used. Data was obtained from journals, books and relevant online sources. The research results show that Canva empowers prospective teachers to create interesting learning materials. Canva encourages student creativity and motivation. Canva also facilitates the development of digital skills essential for 21st century learning.